2012
DOI: 10.4049/jimmunol.1102182
|View full text |Cite
|
Sign up to set email alerts
|

Redundant and Antagonistic Functions of Galectin-1, -3, and -8 in the Elicitation of T Cell Responses

Abstract: Galectins, a family of mammalian lectins, have emerged as key regulators of the immune response. We previously demonstrated that galectin (Gal)-8, from the tandem-repeat subgroup, exerts two well-defined effects on mouse naive peripheral CD4 T cells: Ag-specific costimulation and Ag-independent proliferation. These stimulatory signals on naive T cells have not been described for any other Gal. Therefore, we investigated whether Gal-1 and Gal-3, two prominent members of the Gal family, share the stimulatory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 38 publications
3
57
0
Order By: Relevance
“…Gal-3 showed a suppression of IL-6, indicating a TH1-mediated suppression of inflammation in this model of colitis. These findings are in accordance with published data where gal-3 was capable to suppress T-cell responses [44] .…”
Section: Discussionsupporting
confidence: 83%
“…Gal-3 showed a suppression of IL-6, indicating a TH1-mediated suppression of inflammation in this model of colitis. These findings are in accordance with published data where gal-3 was capable to suppress T-cell responses [44] .…”
Section: Discussionsupporting
confidence: 83%
“…Recently, we showed that aTS but not iTS pushes isolated B cells to produce IL-17 through the activation of the CD45 pathway and sialyl pattern modification (47). T cells might also be modulated through a lectin pathway, as galectins activate T cells through CD45 (48), an effect that might be mimicked by the lectinlike activity of TSs. Unlike B or CD8 T cells, where a direct effect can be observed, thymocytes and CD4 T cells require an interaction with other cell type(s) to be affected by TSs.…”
Section: Discussionmentioning
confidence: 99%
“…In the immune system Gal-8 can play important roles in the homeostasis of T- Tribulatti et al, 2007;Norambuena et al, 2009;Tribulatti et al, 2009;Tribulatti et al, 2012) and B-cells (Tsai et al, 2011). Gal-8 expression in the thymus and its pro-apoptotic eff ects on CD4 high CD8 high thymocytes suggest a role in shaping the T cell repertoire (Tribulatti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%